Analysis of stability and vibrations of porous power and sigmoid functionally graded sandwich plates by the R-functions method - Kurpa, Lidiya V.; Shmatko, Tetyana V.; Linnik, Anna B. (Anatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2023)
In this paper, the R-functions method is used for the first time to study the stability and vibrations of porous functionally graded (FG) sandwich plates with a complex geometric shape. It is assumed that the face layers of the plate are made of functionally graded materials, and the middle layer is isotropic, namely ceramic. Differential equations of motion were obtained using the first-order shear deformation theory with a given shear coefficient (FSDT). Two models of porosity distribution according to the power (P-law) and sigmoid (S-law) laws were studied. Analytical expressions for calculating the effective mechanical characteristics of functionally graded materials with even and uneven porosity distribution were obtained. Proposed approach takes into account the fact that the subcritical state of the plate can be heterogeneous, and therefore, first of all, the stresses in the middle plane of the plate are determined, and then the eigenvalue problem is solved in order to find the critical load. To determine the critical load and plate frequencies, the Ritz method combined with the R-functions theory was used. Developed algorithms and software are tested on case studies and compared with known results obtained by another methods. A number of problems of stability and vibrations of the porous functionally graded sandwich plates with a complex geometric shape for various layer arrangement schemes, various boundary conditions and laws of porosity distribution have been solved.

У даній роботі вперше застосовано метод R-функцій для дослідження стійкості та коливань пористих функціонально-градієнтних сендвіч-пластин зі складною геометричною формою. Припускається, що зовнішні шари пластини виготовлено із функціонально-градієнтних матеріалів, а заповнювач є ізотропним, а саме керамічним. Диференціальні рівняння руху одержано за допомогою звичайної зсувної деформаційної теорії першого порядку із заданим коефіцієнтом зсуву (FSDT). Досліджено дві моделі розподілення пористості згідно із степеневим (P-law) і сигмовидним (S-law) законами. Одержані аналітичні вирази для обчислення ефективних механічних характеристик функціонально-градієнтних матеріалів при рівномірному й нерівномірному розподіленні пористості. Запропонований підхід враховує той факт, що докритичний стан пластини може бути неоднорідним, і тому перш за все визначаються напруження в серединній площині пластини, а потім розв’язується задача на власні значення з метою знаходження критичного навантаження. Для визначення критичного навантаження і частот пластин використано метод Рітца разом із теорією R-функцій. Розроблені алгоритми і програмне забезпечення перевірені на тестових прикладах і порівняні з відомими результатами, одержаними за допомогою інших методів. Вирішено ряд задач стійкості й коливань пористих функціонально-градієнтних сендвіч-пластин зі складною геометричною формою для різних схем укладання шарів, різних крайових умов і законів розподілення пористості.
Аналіз стійкості та коливань пористих степеневих та сигмовидних функціонально-градієнтних сендвіч-пластин методом R-функцій
Keywords: stability; vibrations; sandwich plates; porosity; functionally graded material; R-functions method; Ritz method; стійкість; коливання; сендвіч-пластини; пористість; функціонально-градієнтний матеріал; теорія R-функцій; метод Рітца